PENGUATAN KAPASITAS TOKOH AGAMA DALAM UPAYA PERCEPATAN PENURUNAN PREVALENSI STUNTING DI WILAYAH KECAMATAN ROTE BARAT LAUT, KABUPATEN ROTE NDAO - Picauly, Intje; Tira, Deviarbi Sakke; Wahyuni, Maria M. D. (Jurnal Pengabdian pada Masyarakat Kepulauan Lahan Kering, 2025)
The problem of stunting has a significant impact on the development of human resource quality. SSGI data (2024) states that NTT Province in 2024 contributed the highest prevalence of stunting (37.9%) in Indonesia (19.8%). Rote Ndao Regency is one of the regencies that also contributed a lot of stunted children (18.8%) among the 22 regencies/cities in NTT. This community service activity was carried out with the aim of 1). improving the perception and perspective of religious leaders regarding food, nutrition and health including stunting, 2). religious leaders are able to assess the nutritional status of individuals or community groups and are able to prepare a Diverse, Nutritious, Balanced and Safe (B2SA) menu using counseling and simulation methods in the Busalangga Village Service Area, Northwest Rote District, Rote Ndao Regency in July 2025. The results showed that there was a change in the level of knowledge and attitudes about food, nutrition and health including stunting and its determinants, religious leaders were able to prepare a B2SA menu and use nutrition discs properly. It is recommended that the Rote Ndao district government support the formation of the behavior and perspectives of religious leaders so that they are able to play a perfect role as good partners of the government suzuyatogel